Russian Genocide in Ukraine as an Attempt to Destroy the Ukrainian Nation - Pylypenko, Volodymyr (Review of European and Comparative Law, 2023)
The article assesses the recent and ongoing criminal acts of the Russian Federation in terms of their compliance with existing international crimes, in particular with the crime of genocide, with the aim of correct criminal-law qualification. It provides an analysis of actus reus of genocide as an international crime under the Convention on the Prevention and Punishment of the Crime of Genocide (hereinafter: Convention). The illegal action of the Russian Federation is analysed in the context of the so-called “denazification,” as the main goal of the full-scale aggression of Ukraine. The author attempts to show the distinction between the groups protected by the aforementioned Convention and the term “Nation,” which seems to have much broader sense. The author also concludes that the actus reus of the Russian perpetrators is not aimed solely at the destruction of any of the groups of the Convention, but actually at the destruction of the Ukrainian nation, its culture, language, history and statehood. In this context, the views of Raphael Lemkin, the founder of the concept of genocide as an international crime, are analysed. The necessity of international legal qualification of the actions of the Russian Federation as a new international crime has been substantiated and its conditional name – “natiocide” is proposed.